2021
DOI: 10.1016/j.bbi.2021.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effect on mood in obese patients is determined by the initial gut microbiota composition: A randomized, controlled trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“… 57 In obese patients, 3 months of inulin supplementation improved emotional competence and cognitive flexibility. 58 A recent study in patients suffering from coronary artery diseases has shown that the co-supplementation with 15 g of inulin and Lactobacillus rhamnosus GG during 2 months decreased significantly depression and anxiety scores as well as lipopolysaccharide and inflammatory markers. 59 …”
Section: Discussionmentioning
confidence: 99%
“… 57 In obese patients, 3 months of inulin supplementation improved emotional competence and cognitive flexibility. 58 A recent study in patients suffering from coronary artery diseases has shown that the co-supplementation with 15 g of inulin and Lactobacillus rhamnosus GG during 2 months decreased significantly depression and anxiety scores as well as lipopolysaccharide and inflammatory markers. 59 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in a cohort of healthy females a reduction in preclinical anxiety after a galactooligosaccharide (GOS) intervention was observed [ 19 ▪ ], whereas no effect on depressive symptoms was detected in a population with Major Depressive Disorder (MDD) using the same prebiotic (GOS) [ 9 ]. Similar to probiotic interventions, future studies using prebiotics should also consider the impact of host factors, such as baseline microbiota composition [ 20 ▪▪ ], as well as dose and study duration, when evaluating the efficacy or prebiotics in supporting mental health.…”
Section: Prebioticsmentioning
confidence: 99%
“…Genomic DNA was extracted using a PSP ® spin stool DNA kit (Stratecbiomolecular). Sequencing and subsequent bioinformatics were performed as previously described [ 18 ]. For the gut microbiota analysis, raw sequences can be accessed in Sequence Read Archive database (SRA accession numbers PRJNA595949).…”
Section: Methodsmentioning
confidence: 99%
“…R Software (version 3.5.1, MixOmics package), JMP Pro 14, and Graphpad Prism 8.0 were used for analyses. Mood score was based on the positivity score (Positive scale of the PANAS-Negative scale) as previously described [ 18 ]. Segregation was made using the median of the positivity score: individuals with a higher positivity score were assigned to the “High mood score” group while those with lower score were assigned to the “Low mood score” group and were presented as “High” and “Low” in all tables and figures.…”
Section: Methodsmentioning
confidence: 99%